Estimating The Demand Function for Health Services (Civil and Governmental) For A Sampleof Hospitals in Erbil Governorate - Yusra Ihsan Sadeq; Yaseen Othman Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This research aimed to estimate the function of demand for health services in Erbil governorate and to identify the most important main factors that affect the demand for health services for a sample of auditors in private and governmental hospitals. The research tried to answer the question: What are the most important factors that affect the demand for health services? The research relied on the deductive approach to study the determinants of demand for health services by collecting data through a questionnaire for a sample of private and governmental hospitals in Erbil governorate. The research found that the determinants of demand for health services in Erbil governorate are (age, income, number of family members, educational attainment, chronic diseases, and gender), where the estimated coefficients signals were consistent with the economic theory and at high moral levels. The increase in the proportion of the elderly, the income, the number of family members and the increase in the percentage of people with chronic diseases increase the demand for health services, while the high level of educational attainment leads to a decrease in the demand for health services in the governorate. As for the most important proposals, work to expand the range of free health services provided to the poor and those with chronic diseases, as they are the most in demand for these services. Directing private hospitals to provide health services at low wages to the families of martyrs and poor groups.